2021
DOI: 10.1039/d1fo01160j
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of stevia, sucralose and sucrose in citrus–maqui juices on overweight subjects

Abstract: Background: In the last few years, there has been emerging interest in substituting added sugars from juices by other sweeteners to make them healthier. But their long-term effects have been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The present study takes over from previous works [3,7,8], whose results revealed a high presence of bioavailable polyphenols in the beverage studied, and the influence of alternative sweeteners to sucrose on their bioavailability. Therefore, the work measured the interaction of the sex factor in the study with the consumption of the beverage and the added sweetener, using applied-statistics tools to extend the previous results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study takes over from previous works [3,7,8], whose results revealed a high presence of bioavailable polyphenols in the beverage studied, and the influence of alternative sweeteners to sucrose on their bioavailability. Therefore, the work measured the interaction of the sex factor in the study with the consumption of the beverage and the added sweetener, using applied-statistics tools to extend the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted maqui and citrus as relevant sources of bioactive and bioavailable (poly)phenols, mainly anthocyanins and flavanones, respectively, and proposed stevia and sucralose as alternative sweeteners, as drinks elaborated with them showed a higher bioavailability of phenolic compounds than sucrose-sweetened drinks. In [8], a positive relationship between glycaemic response and stevia was assessed, but it was not enough to link the sweetener with determinate diseases. However, in these studies with the maqui citrus beverage, the results were analysed with basic statistical methods that did not allow for the assessing of clear differences between the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…A study that analyzed blends of lemon juice mixed with different berries found that the blend including Maqui was the most interesting in terms of antioxidant capacity, showing reduced effects on acetylcholinesterase and butyrylcholinesterase; moreover, lemon juice mixed with Maqui can be useful to equilibrate redox balance in acute and intense exercise, it reduces glycemia levels in subjects of both sexes, and its composition has a lower glycemic index, with its properties remaining stable during preservation [ 50 , 51 , 52 ]. It is important to note the agent used to sweeten beverages or citrus-Maqui juices, since according to a study the use of non-caloric sweeteners could alter blood homocysteine levels when sucralose is used ( p = 0.001); however, researchers observed a significant increase in IL-10 concentrations when the beverage was sweetened with Stevia [ 53 ]. Other research that analyzed the effect of a citrus-Maqui beverage with sweeteners on male and female consumers found that the use of Stevia regulated trans-ferulic acid levels in women, while sucrose regulated vanillic acid levels in men, concluding that sweeteners may influence the regulation of polyphenols in subjects who consume these drinks [ 54 ].…”
Section: Applications Of Maqui Fruit In the Food Industrymentioning
confidence: 99%
“…The effects of nNAS on lipid metabolism have also been explored in the meta-analysis [48 ▪ ] that included 14 RCTs in which nNAS intake was found not to be related to significant changes in the lipid parameters of triglycerides (-1.31 mg/dl; -5.89 to 3.27), total cholesterol (-2.27 mg/dl; -7.61 to 3.07), low-density lipoprotein cholesterol (1.95 mg/dl; -2.72 to 4.71) and high-density lipoprotein cholesterol (0.06 mg/dl; -0.62 to 0.73). Other works, such as the RCT by Zafrilla et al [49 ▪ ], which included 138 individuals with overweight, evaluated the effects on markers of oxidative stress, lipid metabolism and inflammatory markers of nNAS, specifically sucralose, compared with stevia and sucrose. An increase in homocysteine levels after consumption of sucralose (27%; P = 0.001) and sucrose (40%; P = 0.006) as well as a significant increase in total cholesterol levels after consumption of sucralose ( P = 0.039) and sucrose ( P = 0.001) were found.…”
Section: Non-nutritive Artificial Sweetenersmentioning
confidence: 99%